A Comprehensive Literature Review of Anticholinergic Drug Exposure and the Risk of Dementia - Pratiwi, Pratiwi; Elsa, Elsa; Aditya, Aditya (International Medical Journal Corp. Ltd, 2024)
Background: The literature surrounding anticholinergic drug exposure and its association with dementia has expanded significantly, revealing critical insights into the risks these medications pose, particularly for older adults. The foundational work by (Campbell et al., 2009) established the prevalence of anticholinergic medication use in this vulnerable demographic and highlighted serious cognitive side effects, including attention deficits and hallucinations. This concern is underscored by physiological changes in older adults that increase their susceptibility to such drugs, suggesting that clinicians must carefully weigh the risks versus benefits when prescribing anticholinergic medications. Literature Review: The cumulative effects of anticholinergic drug exposure were examined in detail by (A. C. Coupland et al., 2019), who found a significant correlation between higher cumulative use and increased dementia risk. This study emphasizes the importance of evaluating long-term medication regimens in older patients, particularly those on multiple prescriptions that may include anticholinergic agents. The findings support the notion that while short-term use can lead to immediate cognitive deficits, the long-term implications are critical and warrant further investigation. Conclusion: In conclusion, the body of literature increasingly points towards a significant association between anticholinergic drug exposure and the risk of dementia, particularly in older adults. While certain medications may carry lesser risks, the cumulative exposure to anticholinergic agents appears to be a critical factor in cognitive decline. Ongoing research is essential to clarify these relationships and guide clinical decision-making, ensuring that the prescribing of anticholinergic medications is conducted with a thorough understanding of their potential long-term cognitive implications.